Cover Picture: Metalated Hexaphyrins: From Understanding to Rational Design (Chem. Eur. J. 49/2015). Issue 49 (1st December 2015) - Alonso, Mercedes; Pinter, Balazs; Geerlings, Paul; De Proft, Frank
Abstract : The unpredictable behavior of [26]‐ and [28]hexaphyrins upon metalation is elucidated by M. Alonso et al. in their Full Paper onpage 17631 ff. Quantum chemical calculations demonstrate that the molecular topology of Group 10 and Group 11 metal complexes of hexaphyrins depends on sensitive interplay between the intrinsic ligand strain and the metal–ligand interaction strength. As such, the aromaticity of the ligand and effective charge of the metal are revealed as key factors determining the binding mode and the preference for Möbius or Hückel structures.